A Mitochondrial tRNA Mutation Causes Axonal CMT in a Large Venezuelan Family. Issue 4 (29th August 2020) - Fay, Alexander; Garcia, Yngo; Margeta, Marta; Maharjan, Sunita; Jürgensen, Claudia; Briceño, Jose; Garcia, Mariaelena; Yin, Sitao; Bassaganyas, Laia; McMahon, Thomas; Hou, Ya‐Ming; Fu, Ying‐Hui; et al.
Abstract : Objective: The objective of this study was to identify the genetic cause for progressive peripheral nerve disease in a Venezuelan family. Despite the growing list of genes associated with Charcot‐Marie‐Tooth disease, many patients with axonal forms lack a genetic diagnosis. Methods: A pedigree was constructed, based on family clinical data. Next‐generation sequencing of mitochondrial DNA (mtDNA) was performed for 6 affected family members. Muscle biopsies from 4 family members were used for analysis of muscle histology and ultrastructure, mtDNA sequencing, and RNA quantification. Ultrastructural studies were performed on sensory nerve biopsies from 2 affected family members. Results: Electrodiagnostic testing showed a motor and sensory axonal polyneuropathy. Pedigree analysis revealed inheritance only through the maternal line, consistent with mitochondrial transmission. Sequencing of mtDNA identified a mutation in the mitochondrial tRNA Val ( mt‐tRNA Val ) gene, m.1661A>G, present at nearly 100% heteroplasmy, which disrupts a Watson–Crick base pair in the T‐stem‐loop. Muscle biopsies showed chronic denervation/reinnervation changes, whereas biochemical analysis of electron transport chain (ETC) enzyme activities showed reduction in multiple ETC complexes. Northern blots from skeletal muscle total RNA showed severe reduction in abundance of mt‐tRNA Val, and mildly increased mt‐tRNA Phe, in subjects compared with unrelated age‐ and sex‐matched controls. Nerve biopsies from 2 affected family members demonstrated ultrastructural mitochondrial abnormalities (hyperplasia, hypertrophy, and crystalline arrays) consistent with a mitochondrial neuropathy. Conclusion: We identify a previously unreported cause of Charcot‐Marie‐Tooth (CMT) disease, a mutation in the mt‐tRNA Val, in a Venezuelan family. This work expands the list of CMT‐associated genes from protein‐coding genes to a mitochondrial tRNA gene. ANN NEUROL 2020;88:830–842